Cost-effectiveness of a primary care based physical activity intervention in 45-74 year old men and women: a randomised controlled trial. Issue 3 (September 1998) - Stevens, W; Hillsdon, M; Thorogood, M; McArdle, D
Abstract : OBJECTIVE: To assess the cost-effectiveness of a primary care based intervention aimed at increasing levels of physical activity in inactive people aged 45-74. METHODS: A total of 714 inactive people aged 45-74, taken from two west London general practices, were randomised into two groups. Intervention subjects were invited to a consultation with an exercise development officer, and offered a personalised 10 week programme to increase their level of regular physical activity, combining leisure centre and home based activities. Control subjects were sent information on local leisure centres. All subjects were followed up at eight months. RESULTS: There was a net 10.6% (95% confidence interval 4.5 to 16.9%) reduction in the proportion of people classified as sedentary in the intervention group compared with the control group, eight months after the intervention. The intervention group also reported an increase in the mean number of episodes of physical activity per week, as compared with the control group (an additional 1.52 episodes (95% confidence interval 1.14 to 1.95)). The cost of moving a person out of the sedentary group was shown to be less than 650 Pounds. The cost of moving someone to the now commonly recommended level was estimated at almost 2500 Pounds. CONCLUSIONS: Moderate physical activity can be successfully encouraged in previously sedentary men and women aged 45-74 through a primary care based intervention. The process of recruitment was the most important variable cost. A high uptake rate would maximise cost-effectiveness, and sensitivity analysis suggests that unit costs could be halved with a more effective recruitment strategy.